2000
DOI: 10.1103/physreva.61.053815
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic instability and locking of pulsation frequencies in free-running two-mode class-B lasers

Abstract: We report on recent experimental results of the dynamics of a laser-diode-pumped free-running Nd:YVO 4 laser operating in a two-mode regime. We observe intrinsic quasiperiodic and chaotic oscillations as well as a locking of pulsation frequencies. We perform an asymptotic analysis of model rate equations in which an intensity-dependent cross-gain ͑i.e., nonlinear gain͒ mechanism of direct mode-mode coupling is introduced in addition to the coupling mechanism via cross saturation of population inversions. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although continuous-wave microchip solid-state lasers are widely used to study the nonlinear effects such as chaos, antiphase dynamics and instabilities [2][3][4][5][6], most of the works are done on the Nd doped gain medium. Coherent, switchable laser pulses with high peak power are required for optical communications and material processing; compact LD end-pumped passively Q-switched solid-state lasers will be potential laser sources for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…Although continuous-wave microchip solid-state lasers are widely used to study the nonlinear effects such as chaos, antiphase dynamics and instabilities [2][3][4][5][6], most of the works are done on the Nd doped gain medium. Coherent, switchable laser pulses with high peak power are required for optical communications and material processing; compact LD end-pumped passively Q-switched solid-state lasers will be potential laser sources for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…In optics, frequency-locking phenomena have been extensively studied in modulated semiconductor lasers, where an external frequency can be readily coupled to the nonlinear system by using a radio-frequency (RF) source 11 , 15 18 , and the hierarchy of the Farey tree and structure of a devil’s staircase can be rather easily observed when tuning the external frequency 11 . Frequency locking has also been demonstrated in other laser structures, such as fibre lasers with external loss modulation 19 or solid-state lasers operating in a two-mode regime 20 . Furthermore, although not explicitly mentioned by the authors, the subharmonic, harmonic, and rational harmonic operation regimes of Kerr microresonators that were reported in refs.…”
Section: Introductionmentioning
confidence: 99%
“…This class of lasers is of greatest importance for application, as it includes most of the high-demand laser types (solid-state, semiconductors). Class-B lasers exhibit especially complex spatio-temporal dynamics associated with the competition of either longitudinal modes [19][20][21] or transverse modes in smallarea lasers [22][23][24][25]. It was also found that in broad-area class-B lasers filamentary instabilities become especially wellpronounced.…”
Section: Introductionmentioning
confidence: 99%